Decent Citizens Serving Chauvinism. Social Portrait of Students Participating in the Blockade of the University of Warsaw in 1936 - Mrzygłód, Izabela (Acta Poloniae Historica, 2022)
November 1936 saw the blockade of the University of Warsaw, an occupational strike organised by far-right students demanding the introduction of the so-called ‘ghetto benches’ for Jewish students. This article draws a social portrait of the ordinary participants in the blockade and analyses their motivations. I argue that the socialisation of youth into exemplary citizens of a modern nation-state created a fertile ground for far-right organisations and their demands. Moreover, the largest student association, the Fraternal Aid Society, became a space for self-organisation into extreme nationalist politics. Its leaders tapped into the positive motivations of youth, i.e. the search for a sense of belonging and the desire of individuals to fit into the normative order of the community. My examination of the blockade offers a unique insight into the academic background of the far-right and its means of political mobilisation.